Perbandingan Jumlah Membership Dan Model Fuzzy Terhadap Perubahan Suhu Pada Inkubator Penetas Telur - Dini Ismawati; Dahnial Syauqy; Barlian Henryranu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Incubator's Ideal temperature is one of important factors that need to consider in egg hatching process. By designing an automation system using fuzzy logic, the ideal temperature can be maintained. The system using NI LabVIEW as graphical programming language software to design the user interface monitoring temperature in incubator. There are few membership functions and models in fuzzy logic. However, still there is no guideline about selection of membership amount and fuzzy model of parameters that using in fuzzy process. In this research, compare and analyze the difference between system that didn't using fuzzy logic and system that using fuzzy logic with variant amount of memberships, those are 3, 5 and 7 memberships, where in each variant is using different model, those are Gaussian, Trapezoid, and Triangle. Based on the result of testing, difference of those three variant memberships is 12.9 and difference of those three fuzzy models is 0.8. Furthermore, amount of membership affects the output of fuzzy system, while fuzzy model is not really affected the output fuzzy system. In temperature testing, the result shows the system that didn't using fuzzy logic method took a long time to reach ideal temperature rather than system that using fuzzy logic method. Fuzzy system that using 7 memberships got smallest difference is 0.49 and took fastest time to get ideal temperature.